Structural and optical characterization of vertical GaAs/GaP core-shell nanowires grown on Si substrates - Kang, J; Gao, Q; Joyce, H; Kim, Y; Guo, Y; Xu, H; Zou, J; Fickenscher, M; Smith, L; Jackson, H; Yarrison-Rice, J; Tan, H; et al. (2010)
GaAs nanowires were grown on Si (111) substrates. By coating a thin GaAs buffer layer on Si surface and using a two-temperature growth, the morphology and crystal structure of GaAs nanowires were dramatically improved. The strained GaAs/GaP core-shell nanowires, based on the improved GaAs nanowires with a shell thickness of 25 nm, showed a significant shift in emission energy of 260 meV from the unstrained GaAs nanowires. © 2010 IEEE.